Neutralización de las actividades tóxicas y enzimáticas de cuatro venenos de serpientes de Guatemala y Honduras por el antiveneno polivalente producido en Costa Rica - Rojas Céspedes, Gustavo (1987)
We studied the ability of the polyvalent antivenom produced in Costa Rica to neutralize lethal, hemorrhagic, edema-forming, proteolytic, hemolytic, hyaluronidase and fibrinolytic activities of the venoms of Bothrops asper and B. nummifer from Honduras, and of Agkistrodon bilineatus and Crotalus durissus durissus from Guatemala. Neutralizing ability of antivenom was expressed as ED50 (effective dose 50%), defined as the antivenom/venom ratio at which the activity of the venom is reduced 50%. Antivenom is highly effective in the neutralization of lethal, hemorrhagic, hemolytic, hyaluronidase, and caseinolytic activities of B. asper, B. nummifer, and C. d. durissus venoms. In the case of B. nummifer venom, neutralization of fibrinolytic effect was only partial, whereas this activity was adequately neutralized when studying the venoms of B. asper and C. d. durissus. The venom of A. bilineatus was adequately neutralized by the antivenom, with the only exception of hemolytic effect that was reduced only partially. However, in quantitative terms, a relatively large volume of antivenom was required to neutralize some effects induced by A. bilineatus venom. Regarding edema-forming activity, antivenom neutralized efficiently the venoms of B. asper and A. bilineatus, whereas that of B. nummifer was neutralized only partiaIly; on the other hand, edema induced by the venom of C. d. durissus was not neutralized at all. Immunochemical results indicate a cIose immunological relationship between venoms of B. asper, B. nummifer and C. d. durissus coIlected in Honduras and Guatemala with those of the sarne species collected in Costa Rica. Interspecies com parison, however, showed variation between venoms obtained from different species. lt is concIuded that, with the exception of edema-forming activity of C. d. durissus and B. nummifer venoms, the polyvalent antivenom produced in Costa Rica is effective in neutralizing the venoms of these four species of crotaline snakes.